CD-ROM Acrobat Journals Using Networks - Brailsford, David F.; Harrison, Leon (British Computer Society, 1994)
The available technologies for publishing journals electronically are surveyed. They range from abstract representations, such as SGML, concerned largely with the structure of the document, to formats such as PostScript which faithfully model the layout and the appearance. The issues are discussed in the context of choosing a format for electronically publishing the journal: Electronic Publishing -- Origination, Dissemination and Design. PostScript is neither widely enough available nor standardised enough to be suitable; a bitmapped pages approach suffers from being resolution-dependent in terms of the visual quality achievable. Reasons are put forward for the final choice of Adobe s new PDF document standard for creating electronic versions of the journal.